Norfloxacin, a Fluoroquinolone Antibiotic, Inhibits Langerhans Cell-Mediated Th1 and Th2 Cell Development - Katsuhiko Matsui; Azusa Kashima; Ayaka Motegi (Frontiers Media S.A., 2019)
Background: It is widely acknowledged that Langerhans cells (LCs) play a primary role in the polarization of T helper type 1 (Th1) or T helper type 2 (Th2) immune responses. Our aim was to find fluoroquinolone ("new quinolone") antibiotics that would inhibit LC-mediated Th2 cell development. Methods: Expression of LC surface molecules was investigated using the reverse transcriptase polymerase chain reaction. The effects of fluoroquinolone antibiotics on T-cell immunoglobulin and mucin domain-containing protein (TIM)-4 expression in LCs were examined to predict whether they would inhibit Th2 cell development. Mice were primed via the hind footpad with ovalbumin (OVA) peptide-pulsed LCs that had been treated with a selected fluoroquinolone antibiotic, then 5 days later the cytokine response in popliteal lymph nodes was examined by enzyme-linked immunosorbent assay. Results: Norfloxacin was selected as a candidate inhibitor of Th2 cell development. As expected, OVA peptide-pulsed LCs that had been treated with norfloxacin and injected into the hind footpads of mice inhibited Th2 cell development, as represented by down-regulation of interleukin (IL)-4 production, as well as Th1 cell development, as represented by down-regulation of interferon (IFN)- g production. This additional inhibition of Th1 cell development was accompanied by suppression of CD40 expression in LCs. In addition, Staphylococcus aureus strains isolated from skin lesions of patients with atopic dermatitis (AD) were more susceptible to norfloxacin than to gentamicin. Topical treatment with norfloxacin significantly suppressed the increase in the skin severity score in NC/Nga mice with AD-like skin lesions. This suppressive effect was associated with a decrease in the production of IFN-g and IL-4 in auricular lymph node cells. Conclusions: The present results show that topical application of norfloxacin inhibits the development of AD-like skin lesions in NC/Nga mice. This suggests that topical application of norfloxacin to AD lesions colonized with S. aureus would act on both superficial S. aureus and epidermal LCs, thus possibly inhibiting the development of Th1 and Th2 cells in vivo, and controlling the severity of AD.